2015
DOI: 10.1007/s00404-015-3825-8
|View full text |Cite
|
Sign up to set email alerts
|

Excessive weight gain during pregnancy and risk of macrosomia: a meta-analysis

Abstract: Our meta-analysis indicated that excessive gestational weight gain might increase the risk of macrosomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
(40 reference statements)
4
25
0
6
Order By: Relevance
“…A meta-analysis among 13 that, as compared to normal maternal pre-pregnancy weight, maternal pre-pregnancy obesity was associated with a 2-fold higher risk of delivering larger sized gestational age infants [17] . Similarly, a meta-analysis among 15 cohort and case-control studies showed that excessive gestational weight gain based on the IOM criteria was associated with a 2-fold higher risk of macrosomia [18] . Based on studies that assessed the associations of gestational weight gain during specific periods of pregnancy, it appears that higher second and third trimester maternal weight gain are especially associated with an increased risk of delivering larger sizes of gestational age infants [19,20] .…”
Section: Fetal Outcomesmentioning
confidence: 99%
“…A meta-analysis among 13 that, as compared to normal maternal pre-pregnancy weight, maternal pre-pregnancy obesity was associated with a 2-fold higher risk of delivering larger sized gestational age infants [17] . Similarly, a meta-analysis among 15 cohort and case-control studies showed that excessive gestational weight gain based on the IOM criteria was associated with a 2-fold higher risk of macrosomia [18] . Based on studies that assessed the associations of gestational weight gain during specific periods of pregnancy, it appears that higher second and third trimester maternal weight gain are especially associated with an increased risk of delivering larger sizes of gestational age infants [19,20] .…”
Section: Fetal Outcomesmentioning
confidence: 99%
“…A multitude of studies have evaluated weight gain in pregnancy among BMI categories and the association with adverse pregnancy outcomes, and the results of this current literature have been inconsistent in the report of outcomes associated with adherence to these guidelines. [2][3][4][5][6][7][8] Keywords ► adverse pregnancy outcomes ► BMI ► gestational weight gain ► institute of medicine Abstract Background It is unclear how adherence to the Institute of Medicine's (IOM) guidelines for weight gain affects pregnancy outcomes. Objectives We investigated how weight gain outside the IOM's recommendations affects the risks of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…A multitude of studies have evaluated weight gain in pregnancy among BMI categories and the association with adverse pregnancy outcomes, and the results of this current literature have been inconsistent in the report of outcomes associated with adherence to these guidelines. [2][3][4][5][6][7][8] In this study, we aimed to evaluate the characteristics of women in early pregnancy in regards to BMI as well as their pattern of weight gain throughout pregnancy (inadequate, appropriate or excessive weight gain) as defined by the IOM. We hypothesized that our population would be composed of more overweight and obese patients and that the majority of patients would not gain within the recommended IOM guidelines.…”
mentioning
confidence: 99%
“…In their study IVS thickness ≥4 mm had sensitivity of 82%, specificity of 22% and with IVS thickness ≥5mm had sensitivity of 53% and specificity of 87%. 9 Karim et al reported that post maturity was associated with macrosomia.…”
Section: Interventricular Septal Thicknessmentioning
confidence: 99%